"المقارنة بين فعالية الجرعات العالية من الديكساميتازون مقابل العلاج بالبريدنزلون في معالجة فرفرية نقص الصفيحات الأساسية الحادة عند الأطفال" - أصلان, سمير; سلوم, علاء (Latakia University Journal -Medical Sciences Series, 2019)
This study included 34 patients aged between 3 months- 12 years who were hospitalized in pediatrics Department at Tishreen University Hospital in Latakia in one year (2017-2018 ) with diagnosis of idiopathic thrompocytopenic purpura by marrow aspiration. The patients were divided into two groups; Group (1): HD-DEXA Group (2) : prednisolon Both methods of treatment were employed , and platelet counts of the patients were determined at diagnosis, and at 2-3-5-7-14-30-90 and 180 days of treatment. Platelet counts were higher in Group (1) The percentages of patients with platelet counts above 20000 plt/mm3 on the 2nd day of the treatment were 88.8% (8 patients) in the first group, and 23.5% (5 patients ) in the second group. The mean time for achievement of platelet counts above 100000 plt/mm3 was (4.2 ) days for the first group, and (21 ) days for the second one . There were significant differences in response to treatment in favor of HD-DEXA. شملت الدراسة 34 مريضاً تراوحت أعمارهم بين 3 أشهر و 12 سنة, قبلوا في قسم الأطفال في مشفى تشرين الجامعي باللاذقية خلال عام واحد (2017 – 2018 ) بتشخيص نقص صفيحات مناعي أساسي. تم تقسيم المرضى الى مجموعتين: المجموعة(1) : HD-DEXA . المجموعة(2) : Prednisolone . تم تطبيق كل خطة علاجية مع تحديد عدد الصفيحات عند التشخيص , وفي الأيام : 2-3-5-7-14-30-90-180 من العلاج. كان ارتفاع تعداد الصفيحات أسرع في مجموعة الـ HD-DEXA . كانت نسبة المرضى الذين تجاوز لديهم تعداد الصفيحات 20 ألف/مم3 في اليوم الثاني من العلاج 88.8% في مجموعة HD-DEXA , بينما بلغت 29.5% في مجموعة الـ Prednisolone . بلغ متوسط عدد الأيام لعودة تعداد الصفيحات للطبيعي (>100ألف/مم3) 4.2 يوم في مجموعة الـ HD-DEXA بينما بلغ 19 يوم في مجموعة الـ Prednisolone . بلغ متوسط عدد أيام الاستشفاء 2.7 يوما في مجموعة الـ HD-DEXA بينما بلغ 5.3 يوم في مجموعة الـ Prednisolone . تبين وجود اختلاف جوهري في سرعة الاستجابة على العلاج لصالح الجرعات العالية من الديكساميتازون .